Transition and justice : negotiating the terms of new beginnings in Africa - Anders, Gerhard; Zenker, Olaf (Development and change (Unnumbered), 2015)
"This book examines a series of cases where peaceful 'new beginnings' have been declared after periods of violence and where transitional justice institutions played a role in defining justice and the new socio-political order"--